Pengembangan Bisnis UMKM Amha Frame dengan Inovasi Perancangan Kotak Tisu Multifungsi Batik dan Kayu - Giovani Tanza; Clairine Jessica; Monica Aguita (Universitas Serang Raya, 2019)
The development of SMEs is very important for the improve welfare of the society and to build the economy of Indonesia.One form of community service that can be done to develop SMEs is to explore the opportunities available in the vicinity. This community service is intended to help provide counseling, motivation and new ideas to SMEs. Amha Frame is SME that crafts and sells wooden frames. From the production of wooden frames, there are materials left over. This service aims to develop products with residual raw materials into multifunctional wooden tissue box from the materials left over comThis service aims to develop products with residual raw materials into bined with Batik to add aesthetic elements. The results of developing ideas that have been formed into batik and wood multifunctional tisue box products have received a positive response from prospective buyers. The most desirable trapezoidal tissue box product from 4 products made.